Pembelajaran Berbasis Masalah dalam Meningkatkan Kemampuan Pemecahan Masalah Matematika - Erna Noviantii; Putri Yuanita; Maimunah Maimunah (Journal of Education and Learning Mathematics Research (JELMaR), 2020)
This study aims to improve the learning process and the student’s mathematical problem solving skill by applying Problem Based Learning (PBL) model. This type of research is classroom action research with two cycles. This research was conducted in collaboration between researcher and teacher of mathematics. Subjects were students of class SMPN 9 Pekanbaru. Study was conducted in the odd semester of academic year 2019/2020. The research instrument consists of mathematical learning instruments and instruments to collect data. Mathematical learning instruments used in this study are syllabus, lesson plans, and activity sheets. Data collection instruments used in this study is observation sheets and mathematical problem solving tests. Data analysis technique in this study is analysis descriptive narrative of qualitative data and descriptive statistical analysis of quantitative data. The result of this study showed that the implementation of PBL improved the learning process and the student’s mathematical problem solving skill. The student’s average value in cycle I which is 70,27 had improved to 84,07 in cycle II. The improvement also found in the indicator average value in understanding the problem (94,99), planning a solution (69,71), implementing the pland (82,77), and checking again (54,85). This study concludes that the implementation of PBL improved the student’s mathematical problem solving skill at class SMPN 9 Pekanbaru.